Media Digital Interaktif dalam Pendidikan Islam untuk Mengembangkan Berpikir Kritis Siswa di Era Masyarakat 5.0 - Siti Luluk Nafisah; Nurhafid Ishari; Qurroti A’yun; Mohammad Darwis (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2026)
Islamic education in the Society 5.0 era integrates high technology into social life, but many Islamic educational institutions still use a teacher-centered approach. This study aims to explore the use of interactive digital media in teaching Islamic education at Madinatul Quran Middle School and Nurul Masyitoh Islamic Middle School in Lumajang. The method used is qualitative with an ethnographic approach, which includes classroom observation, semi-structured interviews, and documentation. The results show that the use of interactive digital media can create a dynamic learning environment, increase student participation, and encourage them to ask questions and develop understanding independently. This study provides a theoretical contribution to the development of competencies of Islamic educational institutions in the Society 5.0 era.